Choral singing with dementia: Examining the experience and impact of embodied and relational musical performance: Developing topics. (7th December 2020) - Smith, Andre P; Erb, Tara; Kampen, Ruth; MacDonald, Stuart; Sheets, Debra J
Abstract: Background: Promising research points to the potential of singing as a novel intervention to improve cognitive function and reduce levels of stress, anxiety, loneliness, and depression in persons with dementia (PwD) (Elliott and Gardner, 2018; Unadkat et al., 2016). This study explores the impact of participation in Voices in Motion (ViM), an intergenerational community choir program designed to engage and support persons with dementia (PwD), their care partners, and students in Victoria, British Columbia, Canada. Combining narrative interviews, focus groups and observations, the study examined care partners and PwD's experiences of ViM and their views of the benefits of choir involvement and considered the impact of ViM on social inclusion and social relationships. Method: Over an 18‐month period, the study initiated and followed two ViM choirs—one active in research for three 3‐month sessions and the other for two sessions of the same time length. Data came from interviews with 23 dyads of PwD and care partners and focus groups with 29 high school students across the two ViM choirs. The interviews and focus groups were conducted at the end of each choir season over the course of the study. Result: The thematic analysis revealed that PwD maintained an embodied ability to learn, experience, and perform songs in the choir despite considerable deficits in cognition, language, and memory. Results indicate that choral participation, as a type of embodied activity, effectively engages PwD and allows them to meaningfully express themselves as both singers and human beings. The ViM choirs facilitated the emergence of strong social relationships between PwD and care partners with the students who reported gaining a deeper and sympathetic understanding of PwD as individuals with rich life stories. Choral singing also served as an inspiring avenue for PwD to develop a strong sense of self and identity as choristers and performers. Conclusion: ViM facilitates the re‐humanization of dementia through well‐attended concerts and performances at public events while also challenging social narratives of decline which remain prevalent in society and stigmatize individuals living with dementia.